The ICSD-3 and DSM-5 guidelines for diagnosing narcolepsy: clinical relevance and practicality. (2nd October 2016) - Ruoff, Chad; Rye, David
Abstract: Narcolepsy is a chronic neurological disease manifesting as difficulty with maintaining continuous wake and sleep. Clinical presentation varies but requires excessive daytime sleepiness (EDS) occurring alone or together with features of rapid-eye movement (REM) sleep dissociation (e.g., cataplexy, hypnagogic/hypnopompic hallucinations, sleep paralysis), and disrupted nighttime sleep. Narcolepsy with cataplexy is associated with reductions of cerebrospinal fluid (CSF) hypocretin due to destruction of hypocretin peptide-producing neurons in the hypothalamus in individuals with a specific genetic predisposition. Updated diagnostic criteria include the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM-5) and International Classification of Sleep Disorders Third Edition (ICSD-3). DSM-5 criteria require EDS in association with any one of the following: (1) cataplexy; (2) CSF hypocretin deficiency; (3) REM sleep latency ≤15 minutes on nocturnal polysomnography (PSG); or (4) mean sleep latency ≤8 minutes on multiple sleep latency testing (MSLT) with ≥2 sleep-onset REM-sleep periods (SOREMPs). ICSD-3 relies more upon objective data in addition to EDS, somewhat complicating the diagnostic criteria: 1) cataplexy and either positive MSLT/PSG findings or CSF hypocretin deficiency; (2) MSLT criteria similar to DSM-5 except that a SOREMP on PSG may count as one of the SOREMPs required on MSLT; and (3) distinct division of narcolepsy into type 1, which requires the presence of cataplexy or documented CSF hypocretin deficiency, and type 2, where cataplexy is absent, and CSF hypocretin levels are either normal or undocumented. We discuss limitations of these criteria such as variability in clinical presentation of cataplexy, particularly when cataplexy may be ambiguous, as well as by age; multiple and/or invasive CSF diagnostic test requirements; and lack of normative diagnostic test data (e.g., MSLT) in certain populations. While ICSD-3 criteria reflect narcolepsy pathophysiology, DSM-5 criteria have greater clinical practicality, suggesting that valid and reliable biomarkers to help standardize narcolepsy diagnosis would be welcomed.